The role and impact of rubber in poly(methyl methacrylate)/lithium triflate electrolyte - Latif, Famiz; Aziz, Madzlan; Katun, Nasir; Ab. Malik Marwan, Alia; Yahya, Muhd Zuazhan (Elsevier BV, 2006)
In this research, new thin freestanding films of poly(methyl methacrylate) (PMMA)/50% epoxidised natural rubber (ENR 50) were doped with lithium triflate, LiCF3SO3 salt was prepared by a solvent casting method. The incorporation of ENR 50 is found to increase the conductivity of PMMA/LiCF3SO3 by two orders of magnitude at room temperature. The highest conductivity achieved was 5.09 Ã— 10-5 S cm-1 at room temperature when 60% of LiCF3SO3 salt was introduced into the PMMA blend containing 10% ENR 50. The formation of excessive hydrogen bonds and interchain crosslinking limit the performance of the blend at higher concentrations of ENR 50. The ionic conduction mechanisms in PMMA/ENR 50/LiCF3SO3 electrolytes obey the Arrhenius rule in which the ion transport in these materials is thermally assisted.